Teaching spirituality to medical students: a systematic review. Issue 3 (3rd July 2022) - Crozier, Dena; Greene, Amy; Schleicher, Mary; Goldfarb, Johanna
Abstract: Purpose: Though it has become increasingly clear that religion and spirituality are important aspects of whole patient care, little is known about how this topic is taught to medical students. This systematic review examined the structure of courses teaching spirituality to medical students and assessed their impact on reported student outcomes. Methods: In October 2020, the authors conducted a systematic review of the literature from 1926 to 2020 to identify published articles describing medical school spirituality curricula. Included studies were English-language articles that described spirituality courses predominantly designed for medical students, specified a curricular structure, and evaluated outcomes of the course. The authors used the Medical Education Research Study Quality Instrument (MERSQI) to assess the quality of the included studies and summarized course structures, curricular content, and study outcomes. Results: Nineteen publications of the 1889 reviewed met the inclusion criteria. These studies were of moderate quality (mean MERSQI = 9.9). The majority of curricula were taught in United States medical schools. Courses were evenly split between mandatory versus elective classes, with mandatory courses having a shorter duration and higher total student participation. Most studies with clear student outcome evaluation had a pre- and post-test design. Common themes throughout the curricula included teaching how to take a spiritual history, delineating differences between spirituality and religion, and experience shadowing chaplains interacting with patients. Conclusions: This broad systematic review of the literature revealed a small but growing number of studies describing specific course structure and curricula for teaching spirituality at the medical student level. For the most concise approach, one short, mandatory didactic session followed by application with standardized or hospital patients can be an effective method of introducing students to the importance of spirituality. Important topics to address include the differences between religion and spirituality, recognizing spiritual distress, how to take a spiritual history, and the relevance of spirituality to student well-being. Measured student outcomes should encompass behavioral changes during patient care in addition to changes in knowledge and attitudes. Suggested methods of evaluation include reflective writing and adding a standardized patient case in which the patient is in spiritual distress in an Objective Structured Clinical Examination (OSCE).